MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density as well as preparation method and application of MoS2 / Ni3S4 / CFP electrocatalyst
By constructing a heterogeneous interface between MoS2 and Ni3S4 to form a three-dimensional petal-like structure, the high cost and scarcity of precious metal catalysts of existing electrocatalytic hydrogen evolution materials is solved, and efficient and stable Electrocatalytic hydrogen evolution reaction.
Patent Information
- Application Number
- CN202411207805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-30
AI Technical Summary
现有的电催化析氢材料如Pt、Pd等贵金属催化剂价格昂贵、储量稀缺,难以大规模工业化利用,且MoS2和Ni3S4基催化剂的活性位点有限和稳定性较差,限制了电解水的工业发展 .
Through hydrothermal reaction, a heterogeneous interface is constructed between MoS2 and Ni3S4. MoS2 and Ni3S4 generate heterojunctions on the carbon paper substrate to form a MoS2/Ni3S4/CFP electrocatalyst with a three-dimensional petal-like structure, regulating the charge distribution and localization of the surface Domain structure, improving catalytic activity and stability.
It realizes a stable current density of MoS2/Ni3S4/CFP electrocatalyst with ampere level, with high reactivity and stability, and can work stably for a long time under high current density, which is suitable for large-scale industrial utilization.
Smart Images

Figure CN119144985A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic hydrogen evolution, and specifically relates to a MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density, and a preparation method and application thereof. Background Art
[0002] Energy and environment are the main issues for sustainable development of human society. The trend of development is to gradually shift from fossil fuels to the use of sustainable and pollution-free non-fossil energy. Hydrogen, as a clean, efficient and sustainable energy carrier, is currently recognized as an ideal substitute for fossil fuels. Electrochemical catalytic decomposition of water is considered to be an efficient and green method for hydrogen production. There are a large number of electrocatalysts that use electrochemical decomposition of water to produce hydrogen (HER). Precious metals such as Pt and Pd show excellent catalytic activity for hydrogen evolution reaction, but they are expensive and scarce, making them difficult to use on a large scale in industrialization, which affects the process of industrial development.
[0003] Among the many candidate materials for electrocatalytic hydrogen evolution, transition metal sulfides (TMSs), such as MoS2 and Ni3S4, have potential applications in electrocatalysis and energy storage and conversion due to their unique physical and chemical properties. MoS2 is a layered compound connected by van der Waals forces, with the upper and lower layers being S atoms and the middle layer being Mo atoms. Theoretical calculations and experiments have shown that the S atoms exposed at its edges have high chemical adsorption energy for H, comparable to that of Pt. Therefore, more and more researchers are committed to developing MoS2-based electrocatalysts, such as synthesizing MoS2 nanomaterials with different morphologies, constructing defective MoS2, and doping other atoms. For example, patent publication number CN 115772681 A discloses a nickel-selenium co-doped molybdenum disulfide catalyst supported on carbon paper, and its preparation method and application. In this method, nickel-selenium co-doped MoS2 is grown vertically on carbon paper in situ, and the edge active sites of the material are fully exposed; the co-doping of nickel and selenium is conducive to the generation of defects; the larger selenium atoms can expand the interlayer spacing of molybdenum disulfide and reduce stacking; these factors are conducive to the nickel-selenium co-doped molybdenum disulfide to exhibit good electrocatalytic hydrogen evolution performance. Patent publication number CN 114318392 A discloses a MoS2-NiS2 / NF hydrogen evolution material and its preparation method and application, wherein sodium molybdate dihydrate, nickel nitrate hexahydrate and urotropine are mixed, and nickel foam is used as a carrier, and MoO2-Ni(OH)2 is loaded on nickel foam through hydrothermal reaction to obtain MoO2-Ni(OH)2 / NF, and then the material and sulfur powder are calcined under anaerobic conditions to form MoS2-NiS2 on nickel foam to obtain MoS2-NiS2 / NF hydrogen evolution material, and strong interaction occurs between MoS2-NiS2 nanoparticles and porous nickel foam in the composite material, so that it has excellent performance in hydrogen evolution reaction. However, the limited active sites and poor stability of the composite material still restrict the development of industrial water electrolysis.
[0004] Constructing a multiphase heterojunction is an effective strategy to improve material stability and promote electron transfer and catalytic kinetics. Ni3S4, as a nickel-based compound with mixed valence states, can provide abundant electrons and effectively promote charge transfer. When Ni3S4 is combined with MoS2, the S atoms with strong electronegativity can capture more electrons from Ni, resulting in the formation of a higher valence state of Ni, which enters the heterojunction as a hydroxyl acceptor, greatly promoting the decomposition of water molecules. However, due to the difficulty in synthesizing Ni3S4, Ni3S4 and Ni3S4-based catalysts are rarely reported. Therefore, it is necessary to develop a new solution to fully utilize the unique physicochemical properties of MoS2 and Ni3S4, while constructing a heterogeneous interface between MoS2 and Ni3S4, and regulating the charge distribution and local structure on their surfaces, so as to design and develop new MoS2-based amperometric electrocatalytic hydrogen evolution materials. Summary of the invention
[0005] In view of the above problems, the present invention provides a MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density, a preparation method and application thereof, a heterogeneous interface is constructed between MoS2 and Ni3S4 through a hydrothermal reaction, and MoS2 and Ni3S4 form a heterojunction on a carbon paper (CFP) substrate to obtain a MoS2 / Ni3S4 / CFP electrocatalyst with a three-dimensional petal-like structure, which has good reaction activity and stability in hydrogen evolution reaction.
[0006] The present invention is achieved through the following technical solutions:
[0007] A MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density is disclosed. A heterogeneous interface is constructed between MoS2 and Ni3S4 through a hydrothermal reaction. MoS2 and Ni3S4 form a heterojunction on a carbon paper substrate to obtain a MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density.
[0008] Furthermore, the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density has a three-dimensional petal-like structure.
[0009] A method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density as described above comprises the following steps:
[0010] (1) Preparation of precursor: nickel salt, urea and ammonium fluoride are dissolved in water and stirred continuously until completely dissolved to obtain a mixed solution A. The mixed solution A and carbon paper are placed in a hydrothermal reactor, sealed and transferred to an oven for a hydrothermal reaction. After the reaction is completed, the carbon paper is taken out and naturally cooled to room temperature. After washing and drying, a nickel hydroxide precursor is obtained.
[0011] (2) Preparation of catalyst: Molybdenum salt and thiourea are dissolved in water and stirred continuously until completely dissolved to obtain a mixed solution B. The mixed solution B and nickel hydroxide precursor are placed in a hydrothermal reactor, which is sealed and transferred to an oven for a secondary hydrothermal reaction. After the reaction is completed, the carbon paper is taken out and naturally cooled to room temperature. After washing and drying, a MoS2 / Ni3S4 / CFP electrocatalyst with a stable ampere-level current density is obtained.
[0012] Furthermore, in step (1), the nickel salt is NiCl2·6H2O, Ni(NO3)2·6H2O or NiSO4·6H2O.
[0013] Furthermore, in step (1), the molar ratio of the nickel salt, urea and ammonium fluoride is 4:7-9:11.5-13; the concentrations of the nickel salt, urea and ammonium fluoride in the mixed solution A are 0.2 mol / L, 0.35-0.45 mol / L and 0.575-0.65 mol / L, respectively.
[0014] Furthermore, in step (1), the primary hydrothermal reaction is carried out at a temperature of 100 to 120° C. for 10 to 12 hours.
[0015] Furthermore, in step (2), the molybdenum salt is (NH4)6Mo7O 24 ·4H2O, MoCl5 or Na2MoO4·2H2O.
[0016] Furthermore, in step (2), the molar ratio of the molybdenum salt to thiourea is 1:7-9; and the concentrations of the molybdenum salt and thiourea in the mixed solution B are 0.05 mol / L and 0.35-0.45 mol / L, respectively.
[0017] Furthermore, in step (2), the secondary hydrothermal reaction is carried out at a temperature of 180 to 200° C. for 22 to 24 hours.
[0018] An application of the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density in hydrogen evolution reaction as described above.
[0019] When preparing the MoS2 / Ni3S4 / CFP electrocatalyst of the present invention, carbon paper (CFP) is added as a substrate. During the reaction, the nickel hydroxide precursor and the MoS2 / Ni3S4 / CFP electrocatalyst are both generated on the carbon paper. When carbon paper is used as a substrate, the hydrophilicity and hydrophobicity of the carbon paper need to be considered. The surface properties of the carbon paper can be changed from hydrophobic to hydrophilic through acid treatment, thereby better adapting to the conditions required for catalyst preparation. Therefore, the carbon paper used in the present invention needs to be used after the following treatment:
[0020] Cut the carbon paper into 2.4cm×2cm specifications, place the cut carbon paper in a round-bottom flask, add concentrated nitric acid to immerse it, then place it in an oil bath for heating and stirring at a temperature of 90-100°C and a rotation speed of 100-200rpm; then immerse it in acetone, ultrasonicate it for 15min, and then rinse it with deionized water; finally, immerse it in ethanol, ultrasonicate it for 15min, and then rinse it with deionized water, soak it in deionized water, and set it aside.
[0021] The preparation principle of the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density of the present invention is as follows:
[0022] (1) In the first hydrothermal reaction, nickel salt is dissolved in water to provide positive divalent nickel ions and hydroxide ions, and nickel hydroxide is generated through a high temperature and high pressure process reaction. The main role of urea is to change the polarity of the solution, further affecting the mass transfer process, and then affecting the morphology of nickel hydroxide crystals; the role of ammonium fluoride is mainly to provide fluoride ions that selectively adsorb on a certain crystal face of nickel hydroxide, thereby changing the crystallization kinetics of each crystal face, and ultimately leading to differences in crystal morphology; carbon paper (CFP) serves as a reaction substrate. Therefore, by controlling the ratio of nickel salt, urea and ammonium fluoride, ultra-thin nickel hydroxide nanosheets are generated on the carbon paper substrate as a precursor for the next hydrothermal reaction.
[0023] (2) In the secondary hydrothermal reaction, a nickel hydroxide precursor, a molybdenum salt and thiourea are mixed. The molybdenum salt provides molybdate and the thiourea provides sulfur ions. The two react to obtain MoS2. At the same time, the sulfur ions react with the nickel hydroxide precursor to obtain Ni3S4. MoS2 and Ni3S4 are combined together through a hydrothermal reaction to generate a MoS2 / Ni3S4 nanoheterojunction on a carbon paper (CFP) substrate, forming a composite material with a specific interface structure, namely, the MoS2 / Ni3S4 / CFP electrocatalyst. In this heterostructure, the different energy band arrangements of different phases will lead to charge transfer at the interface, which is beneficial to the surface electron regulation and the electron transfer rate is improved, so that the composite material has good reactivity and stability in the hydrogen evolution reaction.
[0024] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0025] 1. The present invention constructs a heterogeneous interface between MoS2 and Ni3S4 through a hydrothermal reaction, and MoS2 and Ni3S4 form a heterojunction on a carbon paper substrate to obtain a MoS2 / Ni3S4 / CFP electrocatalyst. This method is different from the one-step hydrothermal synthesis method. The present invention first uses carbon paper as a substrate, and generates a nickel hydroxide precursor on the carbon paper substrate through one-step hydrothermal reaction. In this process, urea and ammonium fluoride are added to the reaction system as structure directing agents, and an ultra-thin nickel hydroxide precursor is obtained by affecting the crystallization kinetics of each crystal face. The nickel hydroxide precursor is then used as a secondary hydrothermal growth substrate and the reaction conditions of the secondary hydrothermal reaction are changed, and the MoS2 / Ni3S4 / CFP electrocatalyst with a stable ampere-level current density is obtained by in-situ sulfurization.
[0026] 2. In the present invention, in the first hydrothermal reaction, the concentrations of urea and ammonium fluoride are controlled at 0.35-0.45 mol / L and 0.575-0.65 mol / L, respectively, so that a nickel hydroxide precursor with a two-dimensional thin sheet structure is generated on the surface of the carbon paper substrate, and the thickness of the thin sheet is thickened. After the second hydrothermal reaction, the composite material has a large number of three-dimensional petal-like structures perpendicular to the substrate. At the same time, in the second hydrothermal reaction, the concentration of thiourea is controlled at 0.35-0.45 mol / L to avoid the formation of NiS and NiS2, so that there is a MoS2 / Ni3S4 heterostructure with two phases coexisting in the composite material, and the reaction time of the second hydrothermal reaction is controlled to 22-24 hours, which is suitable for the growth of MoS2 / Ni3S4 heterojunction, and the three-dimensional nano-petal-like structure formed has a regular morphology and a clear micro-layered structure.
[0027] 3. In the MoS2 / Ni3S4 heterostructure of the present invention, Ni3S4 is a sulfide with mixed valence, i.e., positive divalent and positive trivalent nickel ions. From the XPS graph, it can be seen that Ni in MoS2 / Ni3S4 3+ The content is significantly higher than that of Ni 2+ , and trivalent nickel ions are beneficial to the adsorption of hydroxide, and have lower adsorption free energy for hydroxide than NiS2 and NiS, thereby promoting the dissociation of water molecules.
[0028] 4. The MoS2 / Ni3S4 / CFP electrocatalyst prepared by the present invention has a three-dimensional petal-like structure, a high specific surface area, and a high hydrogen evolution reaction activity. The three-dimensional heterojunction electrode material promotes the electron transfer rate to be improved, and at the same time increases the number of active sites. It shows better hydrogen evolution reaction activity and stability than ordinary two-dimensional materials in the process of water electrolysis. The catalyst is applied to the hydrogen evolution reaction, and the reaction temperature reaches 1A / cm 2 When the current density is 2.5~8.5 W, its overpotential is as low as 268 mV, and it can work stably for 100 h, and can maintain good stability under sudden voltage.
[0029] 5. The preparation method of the present invention is simple in process, easy to operate, mild in conditions, and low in cost. The prepared catalyst has good reactivity and stability in the hydrogen evolution reaction, can work stably for a long time at a high current density of ampere level, has good application value for efficient and green hydrogen production, and is suitable for large-scale industrial utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a low-magnification SEM image of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0031] Figure 2 This is a high-magnification SEM image of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0032] Figure 3 TEM image of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0033] Figure 4 HRTEM image of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0034] Figure 5 This is the XRD pattern of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0035] Figure 6 This is the XPS spectrum of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0036] Figure 7 ECSA image of MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0037] Figure 8 This is the ECSA image of the Ni3S4 / CFP composite nanoelectrode prepared in Comparative Example 1.
[0038] Fig. 9 This is the ECSA image of the MoS2 / CFP composite nanoelectrode prepared in Comparative Example 2.
[0039] Fig.10 Calculated Cdl values of the MoS2 / Ni3S4 / CFP electrocatalyst, Ni3S4 / CFP composite nanoelectrode, and MoS2 / CFP composite nanoelectrode prepared in Example 1 and Comparative Examples 1-2, respectively.
[0040] Fig.11 These are the LSV images of the MoS2 / Ni3S4 / CFP electrocatalyst, Ni3S4 / CFP composite nanoelectrode, MoS2 / CFP composite nanoelectrode, Pt / CFP electrode, and CFP electrode prepared in Example 1 and Comparative Examples 1-4, respectively.
[0041] Fig.12 These are the Tafel images of the MoS2 / Ni3S4 / CFP electrocatalyst, Ni3S4 / CFP composite nanoelectrode, MoS2 / CFP composite nanoelectrode, Pt / CFP electrode, and CFP electrode prepared in Example 1 and Comparative Examples 1-4, respectively.
[0042] Fig.13 It image of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1.
[0043] Fig.14Multi-step It images of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1 measured at different potentials. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0045] Example 1
[0046] Preparation of MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density:
[0047] (1) Preparation of precursor: 4 mmol NiCl2·6H2O, 9 mmol urea and 13 mmol ammonium fluoride were dissolved in 20 mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution A (the concentrations of NiCl2·6H2O, urea and ammonium fluoride in the solution were 0.2 mol / L, 0.45 mol / L and 0.65 mol / L, respectively). 18 mL of the mixed solution A and carbon paper were placed in a hydrothermal reactor, and the carbon paper (CFP) was immersed in the mixed solution A. After sealing, the mixture was transferred to an oven and heated to 120°C for constant temperature reaction for 12 h. After the reaction was completed, the carbon paper was taken out, cooled naturally to room temperature, washed with anhydrous ethanol and deionized water in turn, and dried in an oven at 60°C for 8 h to obtain a nickel hydroxide precursor.
[0048] (2) Preparation of catalyst: Take 1 mmol (NH4)6Mo7O 24 ·4H2O and 9mmol thiourea were dissolved in 20mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution B ((NH4)6Mo7O 24 ·The concentrations of 4H2O and thiourea are 0.05mol / L and 0.45mol / L respectively), 18mL of mixed solution B and nickel hydroxide precursor are placed in a hydrothermal reactor, sealed and transferred to an oven and heated to 200℃ for constant temperature reaction for 24h. After the reaction, the carbon paper is taken out, and the obtained product is naturally cooled to room temperature, washed with anhydrous ethanol and deionized water in turn, and dried in an oven at 60℃ for 8h to obtain MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density.
[0049] Example 2
[0050] Preparation of MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density:
[0051] (1) Preparation of precursor: 4 mmol Ni(NO3)2·6H2O, 8 mmol urea and 12 mmol ammonium fluoride were dissolved in 20 mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution A (the concentrations of Ni(NO3)2·6H2O, urea and ammonium fluoride in the solution were 0.2 mol / L, 0.4 mol / L and 0.6 mol / L, respectively). 18 mL of the mixed solution A and carbon paper were placed in a hydrothermal reactor, and the carbon paper was immersed in the mixed solution A. After sealing, the mixture was transferred to an oven and heated to 110°C for constant temperature reaction for 10 h. After the reaction was completed, the carbon paper was taken out, cooled naturally to room temperature, washed with anhydrous ethanol and deionized water in turn, and dried in an oven at 60°C for 8 h to obtain a nickel hydroxide precursor.
[0052] (2) Preparation of catalyst: 1 mmol MoCl5 and 8 mmol thiourea were dissolved in 20 mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution B (the concentrations of MoCl5 and thiourea in the solution were 0.05 mol / L and 0.4 mol / L, respectively). 18 mL of the mixed solution B and nickel hydroxide precursor were placed in a hydrothermal reactor, which was sealed and transferred to an oven and heated to 190°C for constant temperature reaction for 20 h. After the reaction was completed, the carbon paper was taken out and naturally cooled to room temperature. It was washed with anhydrous ethanol and deionized water in turn, and then dried in an oven at 60°C for 8 h to obtain a MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density.
[0053] Example 3
[0054] Preparation of MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density:
[0055] (1) Preparation of precursor: 4 mmol NiSO4·6H2O, 7 mmol urea and 11.5 mmol ammonium fluoride were dissolved in 20 mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution A (the concentrations of NiSO4·6H2O, urea and ammonium fluoride in the solution were 0.2 mol / L, 0.35 mol / L and 0.575 mol / L, respectively). 18 mL of the mixed solution A and carbon paper were placed in a hydrothermal reactor, and the carbon paper was immersed in the mixed solution A. After sealing, the mixture was transferred to an oven and heated to 100°C for constant temperature reaction for 12 h. After the reaction was completed, the carbon paper was taken out, and the obtained product was naturally cooled to room temperature, washed with anhydrous ethanol and deionized water in turn, and dried in an oven at 60°C for 8 h to obtain a nickel hydroxide precursor.
[0056] (2) Preparation of catalyst: 1 mmol Na2MoO4·2H2O and 7 mmol thiourea were dissolved in 20 mL deionized water and stirred continuously until completely dissolved to obtain a mixed solution B (the concentrations of Na2MoO4·2H2O and thiourea in the solution were 0.05 mol / L and 0.35 mol / L, respectively). 18 mL of the mixed solution B and nickel hydroxide precursor were placed in a hydrothermal reactor, which was sealed and transferred to an oven and heated to 180°C for constant temperature reaction for 24 h. After the reaction, the carbon paper was taken out and naturally cooled to room temperature. It was washed with anhydrous ethanol and deionized water in turn, and then dried in an oven at 60°C for 8 h to obtain a MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density.
[0057] Comparative Example 1
[0058] The difference between Comparative Example 1 and Example 1 is that in step (2) of Comparative Example 1, (NH4)6Mo7O 24 The amount of 4H2O used was 0 mmol, and the rest of the preparation process and conditions were the same as those in Example 1 to obtain a Ni3S4 / CFP composite nanoelectrode.
[0059] Comparative Example 2
[0060] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no nickel hydroxide precursor is added in step (2), and the rest of the preparation process and conditions are the same as those in Example 1 to obtain a MoS2 / CFP composite nanoelectrode.
[0061] Comparative Example 3
[0062] Weigh 5 mg of commercial platinum-carbon catalyst (20%) and pipette 10 μL of Nafion solution (5%) and mix them together in 1 mL of mixed solution (the volume ratio of H2O and EtOH is 1:3) to form a Pt / C catalyst solution. After ultrasonic dispersion, use a pipette to drop it several times on the cleaned carbon paper. After drying, a Pt / CFP electrode is obtained.
[0063] Comparative Example 4
[0064] The cleaned CFP is cut into electrode sizes to obtain a CFP electrode.
[0065] Material Characterization Analysis
[0066] (A) Scanning electron microscopy (SEM) analysis
[0067] Scanning electron microscopy (SEM) was used to characterize the surface morphology of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1. The characterization results are as follows: Figure 1 and 2 As shown. Figure 1It can be seen that under low magnification, the MoS2 / Ni3S4 nanoheterojunction is a three-dimensional nano-petal-like structure obtained by stacking ultra-thin nanosheets and growing evenly on the carbon fiber. Figure 2 It can be seen that under high magnification, the diameter of the three-dimensional MoS2 / Ni3S4 nano-petals is about 2 to 3 μm, and the surface is composed of ultra-thin nanosheets. The three-dimensional nano-petal-like structure obtained by stacking ultra-thin nanosheets has a large specific surface area, which is conducive to the full contact between the catalyst and the electrolyte, and accelerates the efficiency of electron and proton transfer.
[0068] (ii) Transmission electron microscopy (TEM and HRTEM) analysis
[0069] The microstructure of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1 was characterized and analyzed using transmission electron microscopy (TEM and HRTEM). The characterization results are as follows: Figure 3 and 4 As shown. Figure 3 It can be seen that the structure of ultra-thin nanosheets can be observed from TEM, and MoS2 exists on the edge of the nanosheets. Figure 4 It can be seen that the lattice fringes of MoS2 and Ni3S4 can be further observed from HRTEM, corresponding to the MoS2 (002) crystal plane and the Ni3S4 (400) crystal plane, respectively, and clear grain boundaries between the two phases can be seen, indicating that the heterojunction is successfully constructed.
[0070] (III) X-ray diffraction (XRD) analysis
[0071] The crystal structure of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1 was characterized and analyzed by X-ray diffraction (XRD). Figure 5 As shown. Figure 5 It can be seen that the crystal plane can be characterized as diffraction peaks at different incident angles. The XRD spectrum of MoS2 / Ni3S4 / CFP shows that the diffraction peaks at 14.5°, 32.7° and 58.3° correspond to the (002), (100) and (110) crystal planes of MoS2 (JCPDS Card No. 37-1492), while the six sharp diffraction peaks at 16.2°, 26.6°, 31.3°, 37.9°, 50.0° and 54.7° correspond to the (111), (220), (311), (400), (511) and (440) crystal planes of Ni3S4 (JCPDS No. 47-1739). This indicates that Ni3S4 and MoS2 exist in MoS2 / Ni3S4 / CFP.
[0072] (IV) X-ray Photoelectron Spectroscopy (XPS) Analysis
[0073] The surface composition and valence state of the MoS2 / Ni3S4 / CFP electrocatalyst prepared in Example 1 were measured and analyzed by X-ray photoelectron spectroscopy (XPS). Figure 6 As shown. Figure 6 (a) XPS full spectrum shows that there are C, Mo, S, Ni and O elements in MoS2 / Ni3S4; Figure 6 (b) Ni 2p spectra confirm that Ni 2+ and Ni 3+ The presence of Ni2p3 / 2 and 2p1 / 2 in MoS2 / Ni3S4 move toward higher binding energy compared with pure Ni3S4, indicating that the valence state of Ni is higher and the electron cloud density around Ni decreases; Figure 6 (b) Mo 3d spectrum proves that Mo 4+ The presence of , and the Mo 3d 3 / 2 and 3d 5 / 2 in MoS2 / Ni3S4 move toward lower binding energy compared with pure MoS2, indicating that the valence state of Mo is lower and the electron cloud density around Mo is higher; Figure 6 (d) S2p spectra prove that S 2- The presence of Ni3S4 and the shift of S2p3 / 2 and 2p1 / 2 in MoS2 / Ni3S4 to lower binding energy compared with pure MoS2 indicate that the valence state of S is lower and the electron cloud density around S is higher. The change in electron cloud density is attributed to the electronegativity difference between Mo, Ni and S. The introduction of Ni3S4 leads to the rearrangement of the electron cloud at the interface, thus forming a new hybrid structure.
[0074] Electrochemical testing and analysis of materials
[0075] The electrochemical properties of the MoS2 / Ni3S4 / CFP electrocatalyst, Ni3S4 / CFP nanocomposite electrode, MoS2 / CFP nanocomposite electrode, Pt / CFP electrode, and CFP electrode prepared in Example 1 and Comparative Examples 1-4 were tested and analyzed. The materials were tested using CHI 660E and Bio-Logic SAS electrochemical workstations, respectively, with a saturated calomel electrode as the reference electrode, a carbon rod as the counter electrode, and 1 mol / L KOH as the test electrolyte. The prepared samples were electrochemically tested using a three-electrode system at room temperature. Cyclic voltammetry (CV), linear sweep voltammetry (LSV), and chronoamperometry (It) tests were performed using a CHI 660E electrochemical workstation.
[0076] Before testing the samples, the samples were first activated by cyclic voltammetry for 100 cycles at a speed of 100 mV / s in the voltage range of -0.244 to 0.278 V. CV scanning was performed on the samples in the electrolyte to obtain cyclic voltammetry curves of the samples. The scanning speed was 20 to 100 mV / s and the voltage was 0.44 to 0.54 V vs RHE. The electrochemically active surface area (ECSAs) images were plotted through the CV graphs. The ECSA images of the electrodes prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 7 , Figure 8 and Fig. 9 As shown, the CV graph is used to estimate the electrochemical double layer capacitance (Cdl) of the material and plot the graph. The results are shown in Fig.10 In comparison, the ECSA area of the material in Example 1 is larger than that of other materials, and the Cdl value is significantly higher than that of other materials, which is 71.8 mF / cm 2 .
[0077] The LSV was recorded at room temperature with a scan rate of 5 mV / s to obtain the HER polarization curves, such as Fig.11 As shown, the Tafel slope is calculated from the LSV test results, as Fig.12 In the hydrogen evolution reaction, Example 1 reaches 1A / cm 2 At a current density of 2.5 Å, the overpotential is as low as 265 mV and the Tafel slope is 77 mV / dec.
[0078] The stability is obtained by the chronoamperometric test (It), and the test method of It is to adjust the voltage of the sample of Example 1 until the current density is maintained at 1A / cm 2 , a 100-hour stability test was conducted to detect the HER performance. The results are as follows Fig.13 As shown, it can be seen that after 100 hours of stability test, the sample still has high activity.
[0079] At the same time, in order to test the stability of the sample at different potentials, a multi-step chronoamperometry test was performed. The test method of the multi-step chronoamperometry is to adjust the voltage of the sample of Example 1 to a current density of 200, 400, 600, 800, and 1000 mA / cm 2 , including 200, 400, 600, 800, 1000mA / cm 2 One test cycle lasts 12 hours, and there are 4 cycles in total. The total test time is 48 hours. The results are as follows: Fig.14 As shown, it is confirmed that the sample can still maintain good stability under sudden voltage.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density, characterized in that: A heterointerface is constructed between MoS2 and Ni3S4 through hydrothermal reaction, and a heterojunction is formed between MoS2 and Ni3S4 on a carbon paper substrate to obtain a MoS2 / Ni3S4 / CFP electrocatalyst with a stable ampere-level current density.
2. The MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 1, characterized in that: The MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density has a three-dimensional petal-like structure.
3. A method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of precursor: nickel salt, urea and ammonium fluoride are dissolved in water and stirred continuously until completely dissolved to obtain a mixed solution A. The mixed solution A and carbon paper are placed in a hydrothermal reactor, sealed and transferred to an oven for a hydrothermal reaction. After the reaction is completed, the carbon paper is taken out and naturally cooled to room temperature. After washing and drying, a nickel hydroxide precursor is obtained. (2) Preparation of catalyst: Molybdenum salt and thiourea are dissolved in water and stirred continuously until completely dissolved to obtain a mixed solution B. The mixed solution B and nickel hydroxide precursor are placed in a hydrothermal reactor, which is sealed and transferred to an oven for a secondary hydrothermal reaction. After the reaction is completed, the carbon paper is taken out and naturally cooled to room temperature. After washing and drying, a MoS2 / Ni3S4 / CFP electrocatalyst with a stable ampere-level current density is obtained.
4. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 3, characterized in that: In step (1), the nickel salt is NiCl2·6H2O, Ni(NO3)2·6H2O or NiSO4·6H2O.
5. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 4, characterized in that: In step (1), the molar ratio of the nickel salt, urea and ammonium fluoride is 4:7-9:11.5-13; the concentrations of the nickel salt, urea and ammonium fluoride in the mixed solution A are 0.2 mol / L, 0.35-0.45 mol / L and 0.575-0.65 mol / L, respectively.
6. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 3, characterized in that: In step (1), the primary hydrothermal reaction is carried out at a temperature of 100 to 120° C. for 10 to 12 hours.
7. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 3, characterized in that: In step (2), the molybdenum salt is (NH4)6Mo7O 24 ·4H2O, MoCl5 or Na2MoO4·2H2O.
8. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 7, characterized in that: In step (2), the molar ratio of the molybdenum salt to thiourea is 1:7-9; the concentrations of the molybdenum salt and thiourea in the mixed solution B are 0.05 mol / L and 0.35-0.45 mol / L, respectively.
9. The method for preparing the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density according to claim 3, characterized in that: In step (2), the secondary hydrothermal reaction is carried out at a temperature of 180 to 200° C. for 22 to 24 hours.
10. Use of the MoS2 / Ni3S4 / CFP electrocatalyst with stable ampere-level current density as claimed in claim 1 or 2 in hydrogen evolution reaction.
Citation Information
Patent Citations
Preparation method and application of MoS2-NiS2 composite nanosheet electrocatalyst constructed by taking carbon cloth as substrate
CN112376066A
1T-MoS2 / NiS heterogeneous interface structure catalyst for electro-catalytic hydrogen evolution as well as preparation method and application of 1T-MoS2 / NiS heterogeneous interface structure catalyst
CN114318407A
